2022
DOI: 10.1155/2022/4757081
|View full text |Cite|
|
Sign up to set email alerts
|

Delivery of miR-654-5p via SonoVue Microbubble Ultrasound Inhibits Proliferation, Migration, and Invasion of Vascular Smooth Muscle Cells and Arterial Thrombosis and Stenosis through Targeting TCF21

Abstract: Background. Abnormal proliferation of vascular smooth muscle cells (VSMCs) is an important cause of vascular stenosis. The study explored the mechanism of inhibition of vascular stenosis through the molecular mechanism of smooth muscle cell phenotype transformation. Methods. Coronary heart disease-related genes were screened by bioinformatics, and the target genes of miR-654-5p were predicted by dual-luciferase method and immunofluorescence method. miR-654-5p mimic stimulation and transfection of TCF21 and MTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…miR-654-3p is also participated in lncRNA ZDAS1-modulated cholesterol efflux in atherosclerosis [ 36 ]. Delivery of miR-654-5p via SonoVue microbubble ultrasound inhibits proliferation, migration, and invasion of vascular smooth muscle cells and arterial thrombosis and stenosis [ 37 ]. Our present data found that miR-654-3p is downregulated in response to MI and participated in the MI regulation.…”
Section: Discussionmentioning
confidence: 99%
“…miR-654-3p is also participated in lncRNA ZDAS1-modulated cholesterol efflux in atherosclerosis [ 36 ]. Delivery of miR-654-5p via SonoVue microbubble ultrasound inhibits proliferation, migration, and invasion of vascular smooth muscle cells and arterial thrombosis and stenosis [ 37 ]. Our present data found that miR-654-3p is downregulated in response to MI and participated in the MI regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that miR-654-5p is an important gene that regulates VSMC phenotypic transformation. It can inhibit the expression of TCF21 and cell proliferation, invasion, and metastasis [4]. That is, it can inhibit arterial thrombosis and stenosis by targeting TCF21.…”
Section: Targeting Tcf21 Inhibits the Abnormal Proliferation And Migr...mentioning
confidence: 99%
“…Aberrant proliferation of vascular smooth muscle cells (VSMCs) in AS promotes plaque formation, but VSMCs in advanced plaques are beneficial by preventing fibrous cap rupture [3]. Recent studies have found that decreased expression of the transcription factor 21 (TCF21) can inhibit the proliferation and migration of VSMCs and inhibit arterial thrombosis and lumen stenosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%